2018
DOI: 10.3389/fmicb.2018.01574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ferric Oxyhydroxide on Anaerobic Microbial Dechlorination of Polychlorinated Biphenyls in Hudson and Grasse River Sediment Microcosms: Dechlorination Extent, Preferences, Ortho Removal, and Its Enhancement

Abstract: Microbial reductive dechlorination of polychlorinated biphenyls (PCBs) has been observed in many PCB-impacted sediments. However, this biodegradation is relatively site-specific and can be affected by PCB compositions and sediment geochemical conditions. To better understand the influence of a common competing electron acceptor, ferric oxyhydroxide (FeOOH), on dechlorination, two sediments (Hudson River and Grasse River sediments), and two PCB mixtures (PCB 5/12, 64/71, 105/114, and 149/153/170 in Mixture 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Our previous studies found that PCB71 and PCB149 could be extensively dechlorinated in Hudson and Grasse River sediments with similar levels of Dehalococcoides but with a more prevalent methane production. 54,65 It was reported that methanogens might assist dechlorination through the activity of coenzyme F430. 66 The methanogenic coenzyme F430 was demonstrated to significantly reduce the energy barrier to dechlorination.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Our previous studies found that PCB71 and PCB149 could be extensively dechlorinated in Hudson and Grasse River sediments with similar levels of Dehalococcoides but with a more prevalent methane production. 54,65 It was reported that methanogens might assist dechlorination through the activity of coenzyme F430. 66 The methanogenic coenzyme F430 was demonstrated to significantly reduce the energy barrier to dechlorination.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The addition of Fe 3 O 4 increased the dechlorination rate by 1.5-fold, the transfer of electrons from non-dechlorinating bacteria to dechlorinating bacteria was accelerated. However, ferric iron might compete with halogenated organic pollutants for electrons, inhibiting the process of reductive dehalogenation. , Therefore, the high contents of MBC and IP might inhibit the debromination, which potentially explained why MBC at medium doses could facilitate the reductive debromination ratio on the root surfaces rather than those at high doses.…”
Section: Resultsmentioning
confidence: 99%
“…These OHRB preferentially attack metaand/or para-chlorines in PCBs, leaving orthochlorinated PCBs as dechlorination products (Wu et al, 2002;Fennell et al, 2004;Adrian et al, 2009;Wang and He, 2013;LaRoe et al, 2014;Wang et al, 2014;Zhen et al, 2014;Wang et al, 2019). Thus far, several orthochlorine-removing microcosms have been established, e.g., o-17 culture (Cutter et al, 2001;Xu et al, 2018). However, the ortho-chlorine attacking OHRB have continued to elude enrichment and isolation.…”
Section: Bio-rd Of Organohalidesmentioning
confidence: 99%